Locação das estruturas de lazer e cultura como fonte de captação de recursos próprios: o caso da Universidade Federal de Mato Grosso - Mendes, Alessandra Melo da Silva (2024)
In recent years, Federal Higher Education Institutions (IFES) have undergone changes in budgetary scenarios, including a reduction in transfers from the Federal Government, their main financier. Faced with these changes, IFES had to adapt to the scarcity, looking for ways to efficiently apply their resources and/or reduce expenses, without losing their main focus, which is the provision of quality education services. The study addresses the importance of the autonomy of federal public universities, focusing especially on financial autonomy and the need to generate own resources to complement government funding. Autonomy allows institutions to decide on the application of discretionary resources, essential for non-mandatory areas such as research, extension and investments in infrastructure. The research approach used was qualitative, and the methods were traditional literature review and case study. The objective of this dissertation is to propose a guide to assist in pricing the rental of UFMT's leisure and cultural structures, so that they become a source of fundraising. Among the specific objectives are the identification of the main leisure and cultural structures at the Federal University of Mato Grosso, proposing a pricing policy for the rental of these structures and suggesting a resolution to institutionalize the pricing policy based on costs. Through the data collected in the case study, it was possible to identify the items that are contained in the full cost of each structure, extracting those that are paid with discretionary resources, allowing the identification of the effective impacts on the entity's budgetary-financial planning. The study proposes a pricing policy for these structures, aiming to mitigate the financial impact of these infrastructures on the institution's discretionary budget. Clear steps to be followed in implementing this policy were outlined, aiming to institutionalize efficient and transparent management practices. The research is justified by the need to promote efficient public management, which supports the autonomy of universities through the generation of their own revenue. Furthermore, it emphasizes the importance of a strategic cost view for an efficient allocation of resources in the public sector.